The role of amines in paraganglioma, neuroblastoma and carcinoid diagnosis - Tormey, William P. (Trinity College (Dublin, Ireland). Department of Chemical Pathology, 2000)
The role of urinary noradrenaline, adrenaline, dopamine, 4-hydroxy-3-methoxy-mandelic acid (HMMA) and homovanillic acid (HVA) in the diagnosis of paraganglioma especially phaeochromocytoma and in neuroblastoma is investigated. The clinical and laboratory correlates of the association of HMMA and HVA with an increased urinary 5-hydroxyindoleacetic acid (5-HIAA) were also studied. Latterly, the utility of urinary normetanephrine and metanephrine in the diagnosis of phaeochromocytoma was studied. The current clinical practice and relationship of I-metaiodobenzylguanidine scans to biochemical screening for phaeochromocytoma was also studied. The relationship of 24-hour urinary catecholamines, HMMA and HVA to DNA ploidy in 14 patients with phaeochromocytoma was studied. As physiological stress is common before death, catecholamines in urine after death were studied to see if there was a separation from values seen in phaeochromocytoma.
Keywords: Chemical Pathology, Ph.D.; Ph.D. Trinity College Dublin